A Trust Model for Detecting Device Attacks in Mobile Ad Hoc Ambient Home Network - Akinboro, Solomon A; Olajubu, Emmanuel (IGI Global, 2023)
title;A Trust Model for Detecting Device Attacks in Mobile Ad Hoc Ambient Home Network volume number:8 issue no: 2 • April-June 2016